2002
DOI: 10.1016/s1381-1169(01)00425-3
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on hydration of alkynes by the PtCl4–CO catalyst

Abstract: Dedicated to Professor Myron Rosenblum on the occasion of his 75 th birthday in recognition of his outstanding contribution to chemistry AbstractUnder CO atmosphere, between 80 and 120˚C, a glyme solution of PtCl 4 forms a carbonyl compound that promotes hydration of internal as well as terminal alkynes to give aldehyde-free ketones. The catalytic process depends strongly on the electronic and steric nature of the substrates. Part of the carbonyl functions of the catalyst can be replaced by phosphine ligands. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
(23 reference statements)
0
13
0
3
Order By: Relevance
“…Yagupolskii et al 278 carried out an aza Curtius rearrangement by reacting N -(trifluoromethylsulfonyl)carboximidoyl chlorides with sodium azide in monoglyme or acetonitrile at −5 to +10 °C to form carbodiimides RN=C=NSO 2 CF 3 . Israelsohn et al 279 reported that the PtCl 4 -CO catalyst could promote the hydration of internal and terminal alkynes in aqueous monoglyme or diglyme to afford aldehyde-free ketones between 80 and 120 °C. The reaction was found strongly dependent on the electronic and steric nature of the alkynes.…”
Section: Uses In Organic Reactionsmentioning
confidence: 99%
“…Yagupolskii et al 278 carried out an aza Curtius rearrangement by reacting N -(trifluoromethylsulfonyl)carboximidoyl chlorides with sodium azide in monoglyme or acetonitrile at −5 to +10 °C to form carbodiimides RN=C=NSO 2 CF 3 . Israelsohn et al 279 reported that the PtCl 4 -CO catalyst could promote the hydration of internal and terminal alkynes in aqueous monoglyme or diglyme to afford aldehyde-free ketones between 80 and 120 °C. The reaction was found strongly dependent on the electronic and steric nature of the alkynes.…”
Section: Uses In Organic Reactionsmentioning
confidence: 99%
“…The same group reported later that PtCl 4 /CO was a better catalyst for the hydration of alkynes (Scheme 8). [38,89] Moderate yields for both terminal and internal alkynes 59 were found. The mechanism proposed [38] suggests a prereduction of Pt IV to Pt II under CO atmosphere to form the active species 60.…”
Section: Platinum Catalystsmentioning
confidence: 94%
“…[38,89] Moderate yields for both terminal and internal alkynes 59 were found. The mechanism proposed [38] suggests a prereduction of Pt IV to Pt II under CO atmosphere to form the active species 60. The catalytic activity observed for PtCl 2 under similar conditions and X-ray photoelectron spectroscopy (XPS) measurements of the final mixture confirms this reduction.…”
Section: Platinum Catalystsmentioning
confidence: 94%
See 1 more Smart Citation
“…Anfang der 90er Jahre wurde Pt als ein aktiver Katalysator für die Hydratisierung von Alkinen erkannt 38. 8688 Als erstes setzten Jennings und Mitarbeiter das Zeise‐Dimer 47 als Katalysator für die Hydratisierung von endständigen und inneren Alkinen ein (Schema ) 86.…”
Section: Katalytische Aktivitätunclassified